The practice of theory : rhetoric, knowledge, and pedagogy in the academy - Bernard-Donals, Michael F. (New York : Cambridge University Press, 1998)
Examines the connection between theory and its practical application, and explores the extent to which rhetoric can animate the link between theory, teaching, and practice.
Includes bibliographical references (p. 239-246) and index.
Adult
Keywords: Knowledge, Theory of; Language and education; Rhetoric; Rhetoric; Theory of knowledge